Critical Discourse Analysis of U-20 World Cup Cancellation Polemic in Liputan6 Talks - Anugrah, Yuni Esa; Tutiasri, Ririn Puspita (UMSU, 2024)
Football is one of the most popular sports with the highest number of fans and enthusiasts among other sports. Issue about the cancellation of the U-20 World Cup in Indonesia has been widely reported by the media, both television and online media. This intersects with the status and rights of the official World Cup broadcaster obtained by EMTEK, which houses SCTV. The purpose of this research is to find out the discourse built and developed in the Liputan6 Talks episode